A wideband circularly polarized crossed dipole antenna with compact structure and frequency reconfiguration. Issue 7 (4th March 2021) - Li, Wentao; Qu, Haotian; Wang, Yiming; Wei, Meng; Hei, Yongqiang
Abstract: In this letter, a novel wideband circularly polarized (CP) crossed dipole antenna with frequency reconfiguration is proposed. By introducing two quasi‐Sierpinski fractal orthogonal dipoles printed on both sides of the substrate, compact, broadband and low cross‐polarization characteristics are achieved. The proposed antenna can be switched flexibly over two frequency bands via controlling the states of the PIN diodes inserted in each arm of the crossed dipole. The measured −10 dB impedance bandwidths of the antenna are 63% in 2.23–4.27 GHz and 12.5% in 4.04–4.58 GHz, respectively. Meanwhile, the 3 dB axial ratio bandwidths are 34.7% in 2.5–3.55 GHz and 4.16% in 4.23–4.41 GHz, respectively. The proposed antenna is desired to be applied in the future wireless communication systems.